Models for Dynamic Panels in Space and Time - an Application to Regional Unemployment in the EU - J.Paul Elhorst (European Regional Science Association (ERSA), 2005)
One of the central research questions in modelling space-time data is the right econometric model. At least three problems must be tackled: (i) The observations on each spatial unit might be correlated over time, (ii) The observations at each point in time might be correlated over space, and (iii) The omission of time-invariant and/or spatial-invariant background variables could bias the regression coefficients in a typical cross-section or time-series model. As we have no a priori reasons to believe that one problem is more important than another, this paper presents a general model that encompasses a wide series of simpler models frequently used in the time-series econometrics, spatial econometrics and panel data econometrics literature. A framework is developed to determine which model is the most likely candidate to study space-time data.
Keywords: 330